2019
DOI: 10.1001/jamaophthalmol.2019.2919
|View full text |Cite
|
Sign up to set email alerts
|

Association of Giant Cell Arteritis With Race

Abstract: IMPORTANCE Giant cell arteritis (GCA) is the most common vasculitis in adults and is associated with significant morbidity and mortality. Its incidence has been carefully studied in white populations, yet its relevance among other racial and ethnic groups is less well known. OBJECTIVE To examine the incidence of biopsy-proven GCA (BP-GCA) in a tertiary care center-based population with a sizeable proportion of black patients. DESIGN, SETTING, AND PARTICIPANTS This retrospective cohort study identified all pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…One of the most recently published epidemiologic studies did not show a difference in the incidence of GCA based on race. 17 This contradicts previous studies, which reported higher incidences in white and particularly Scandinavian-origin ethnicities. 18 Temporal arteritis is relatively a 'confined' topic as compared with hypertension and diabetes.…”
Section: Discussionmentioning
confidence: 58%
“…One of the most recently published epidemiologic studies did not show a difference in the incidence of GCA based on race. 17 This contradicts previous studies, which reported higher incidences in white and particularly Scandinavian-origin ethnicities. 18 Temporal arteritis is relatively a 'confined' topic as compared with hypertension and diabetes.…”
Section: Discussionmentioning
confidence: 58%
“…In a recent retrospective cohort study comprising 586 patients who underwent temporal artery biopsy (TAB), there was no significant difference in biopsy-positive GCA cases between Caucasian and Afro-Caribbean patients. However, the proportion of Afro-Caribbean patients in the study was only 28.5% [9]. Similarly, in two other retrospective studies, the proportion of non-Caucasian patients was small [10][11].…”
Section: Discussionmentioning
confidence: 65%
“…This study led to the common teaching that GCA is largely a disease affecting White individuals. However, more recent and racially representative studies have demonstrated similar prevalence of GCA between Black and White patients (24). Despite this, ethnicity was still included as an important clinical factor in diagnosis of GCA in the ACR rheumatology guideline (17).…”
Section: Resultsmentioning
confidence: 98%